PENGARUH RETURN ON ASSETS (ROA) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PADA PT INDOFOOD SUKSES MAKMUR TBK PERIODE 2014-2023 - Adelia Puspita Sari; Intan Sari Budhiarjo (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) on the Share Price of PT Indofood Sukses Makmur Tbk for the 2014-2023 Period. The data for this study are the financial statements of PT Indofood Sukses Makmur Tbk taken from www.indofood.com and www.idx.co.id. The sampling used is Return On Assets (ROA) and Debt To Equity Ratio (DER) for 10 years. The method used is descriptive with a quantitative approach. Data analysis using classical assumption test, multiple linear regression, hypothesis testing (partial t test and simultaneous f test), and coefficient of determination analysis using SPSS version 26. The results of the analysis show that the partial t test shows that Return On Assets (ROA) has no effect on stock prices with the test result 1.198 < 2.306 and a significance value (Sig.) 0.270 > 0.05, Debt To Equity Ratio (DER) has no effect on stock prices with the test result -2.252 < 2.306 and a significance value (Sig.) 0.059 > 0.05. In the simultaneous f test Return On Assets (ROA) and Debt To Equity Ratio (DER) have an effect on stock prices with the test results 6.086 > 4.74 and a significance value (Sig.) 0.029 < 0.05. The coefficient of determination proves a value of 0.635, which means that Return on Asset (ROA) and Debt to Equity Ratio (DER) affect the stock price by 63.5%. While the rest, amounting to (100% - 63.5% = 36.5%) is influenced by other variables outside this study.